Numerical Modelling of Milne Fiord 2011-2019 constant BC ... - Bonneau, Jérémie; Mueller, Derek; Laval, Bernard E (Federated Research Data Repository / dépôt fédéré de données de recherche, 2024)
This dataset contains the setup of a three dimensional numerical model of Milne Fiord (Nunavut, Canada) built using MITgcm. It also contains the input and output of the model. The model was run from May 2011 to September 2019. This is a companion dataset to "Numerical Modelling of Milne Fiord 2011-2019; https://doi.org/10.20383/103.0887". The only difference is that this simulation was carried out with constant offshore boundary conditions in order to investigate the role of variable offshore forcing. It also contains the input and output of the model. The model was run from May 2011 to September 2019. For more details, see Bonneau, J., Laval, B. E., Mueller, D., Hamilton, A. K., Antropova, Y. 2024. Heat Fluxes in a Glacial Fjord: The Role of Buoyancy-Driven Circulation and Offshore Forcing. Geophysical Research Letters. ...